Initial Experiences of Simultaneous Laparoscopic Resection of Colorectal Cancer and Liver Metastases. (2nd October 2012) - Hoekstra, L. T.; Busch, O. R. C.; Bemelman, W. A.; van Gulik, T. M.; Tanis, P. J.
Abstract : Introduction . Simultaneous resection of primary colorectal carcinoma (CRC) and synchronous liver metastases (SLMs) is subject of debate with respect to morbidity in comparison to staged resection. The aim of this study was to evaluate our initial experience with this approach. Methods . Five patients with primary CRC and a clinical diagnosis of SLM underwent combined laparoscopic colorectal and liver surgery. Patient and tumor characteristics, operative variables, and postoperative outcomes were evaluated retrospectively. Results . The primary tumor was located in the colon in two patients and in the rectum in three patients. The SLM was solitary in four patients and multiple in the remaining patient. Surgical approach was total laparoscopic (2 patients) or hand-assisted laparoscopic (3 patients). The midline umbilical or transverse suprapubic incision created for the hand port and/or extraction of the specimen varied between 5 and 10 cm. Median operation time was 303 (range 151–384) minutes with a total blood loss of 700 (range 200–850) mL. Postoperative hospital stay was 5, 5, 9, 14, and 30 days. An R0 resection was achieved in all patients. Conclusions . From this initial single-center experience, simultaneous laparoscopic colorectal and liver resection appears to be feasible in selected patients with CRC and SLM, with satisfying short-term results.